Contacts and Keeping Up - A Brief Look at Ongoing and Unpublished Studies and Research in Canada - Baker, Warren C.; Lipinski, Thomas F. (Canadian Journal of Counselling and Psychotherapy, 2012)
Canadian investigators in the areas of psychology and sociology were queried regarding ongoing and/or unpublished research studies, using a mail survey. This was done for the purposes of forming linkages between researchers across Canada working in the areas of aging, and of identifying potential resource persons in geographic areas of Canada. Results suggest that a more complete compilation of studies not available in standard sources will advance research into aging.